The resilience of emergency and critical care nurses: a qualitative systematic review and meta-synthesis - Liu, Shuyang; Zhang, Yu; Liu, Yue; Han, Peng; Zhuang, Yugang; Jiang, Jinxia (Frontiers in Psychology, 2023)
Background: Due to the unique work environment, emergency and critical care departments nurses face high job pressure, often resulting in burnout and a high turnover rate. Public health emergencies such as the Corona Virus Disease 2019 pandemic tend to exacerbate these problems further. Therefore, improving the resilience of nurses is crucial to enhance their retention rates.Objective: This systematic review and meta-synthesis of qualitative studies on the resilience of emergency and critical nurses were conducted to provide a reference for clinical managers to develop strategies for improving the resilience of nurses.